Análise do discurso de sujeitos afásicos e seus familiares sobre afasia. - Costa, Érika Maria Asevedo (2019)
This doctoral thesis is inspired on the author’s master’s dissertation about aphasia, which, in its clinical frame, can range from simple imperceptible speech disorders to total inability to participate in a conversation, affecting people’s interactions and their social and financial sustainability. This language disorder has been traditionally investigated regarding its physiological origin (Strokes or Traumatic Brain Injury, the two most common causes) and medicine interventions in order to evidence, avoid or relieve it, inasmuch as Aphasia is generated due to neurological causes. Since my master’s research, in an innovative way, this study aims at inserting the linguistic-discursive proposal into the discussion concerning Aphasia, by the means of the theoretical and analytical procedures of the French Discourse Analysis (FDA), as a theoretical framework that is able to improve the interpersonal interactions amongst the individuals who suffer from Aphasia, in such a way they will be able to have a faster and more efficient social reframing. Currently, my doctoral research performed a longitudinal investigation which brought the discourse of five subjects from the Grupo de Convivência dos Afásicos (Aphasic Social Group) of the Catholic University of Pernambuco (UNICAP) along with their family members witnessing their words about/of Aphasia. Given the above, this work aimed at analyzing the aphasics’ discourse of/about Aphasia in a social group and in their respective families, understanding the process of imaginary formations, in order to analyze through their words how the event of Aphasia is constituted throughout the individuals’ speech that aims to problematize the image of an aphasic person in a conflictual relationship with language. Insofar as FDA is not only a methodology, but a theoretical framework as well, this work explores some concepts such as: sense, ideology, subject, imaginary formation, discursive formation, production conditions and interdiscourse in this perspective. Meanwhile, I also highlighted the importance of the Aphasic Social Group of UNICAP to the subjects of this research and their family members. The data collection happened from 2015 to 2017 during the weekly meetings of the Aphasic Social Group of UNICAP where the participants had their discourses recorded for the posterior transcription and analysis based on the theoretical and methodological principles of FDA: discourse, production conditions, ideology, subject, interdiscourse, ideological formation, imaginary formation and silencing. The aphasic subjects investigated in this research presented disorders in one of the language axels: selection or combination and, in some cases, in both, according to the typology proposed by Jakobson. The discourses were frequently guided by imaginary formations hence relations of power, inasmuch as they constitute themselves as aphasic subjects from the image they make about themselves and the one they judge their interlocutor makes of them, interacting hierarchically in the group according to their perceptions, life stories and production conditions.